Crack analysis by using the enriched singular boundary method. (November 2016) - Ma, Ji; Chen, Wen; Lin, Ji
Abstract: In this paper, we make the first attempt to extend the singular boundary method to crack problems in conjunction with the domain decomposition technique. In order to characterize singular behaviors around cracks, enriched functions are analytically derived from the governing equations and the corresponding conditions containing singularities. We verify the present enriched singular boundary method to the torsion problem of a cracked bar and the acoustic propagation problem in crack media, which are governed by Laplace and Helmholtz equations, respectively. Numerical results demonstrate the accuracy and efficiency of the proposed scheme.